1998
DOI: 10.1155/1998/865042
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response Protective Effect of Salbutamol on Methacholine Airway Responsiveness using Pressurized Metered Dose Inhalers and Turbuhalers

Abstract: The purpose of this study was to estimate the relative dose potency of salbutamol Turbuhaler compared with salbutamol pressurized metered dose inhaler (pMDI) with respect to the protective effect against methacholine bronchoconstriction. Twenty-three asthmatic subjects with stable asthma participated in the study. Baseline forced expiratory volume in 1 s (FEV 1 ) was 70% or more of predicted, and baseline methacholine provocative concentration causing a 20% fall in FEV 1 (PC 20 ) was 4 mg/mL or less. The desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Also, in the study by LoÈ fdahl (6), the observed dierences in FEV 1 between the lowest and highest dose of salbutamol was quite small, amounting to a mean of 0Á15 l suggesting a quite shallow dose±response curve in the studied patients. In a more recent study, we have been unable to detect any numeric dierences in the improvement in FEV 1 between salbutamol given by the Turbuhaler and pMDI (7), which others also have been unable to detect when evaluating eects of salbutamol on methacholine responsiveness (9).…”
Section: Discussionmentioning
confidence: 58%
“…Also, in the study by LoÈ fdahl (6), the observed dierences in FEV 1 between the lowest and highest dose of salbutamol was quite small, amounting to a mean of 0Á15 l suggesting a quite shallow dose±response curve in the studied patients. In a more recent study, we have been unable to detect any numeric dierences in the improvement in FEV 1 between salbutamol given by the Turbuhaler and pMDI (7), which others also have been unable to detect when evaluating eects of salbutamol on methacholine responsiveness (9).…”
Section: Discussionmentioning
confidence: 58%
“…In a similar study, in which 23 asthmatic patients were submitted to methacholineinduced bronchoconstriction, Wong et al (15) reported that the protective effect of salbutamol against bronchoconstriction was more pronounced when the drug was delivered via Turbuhaler than when delivered via MDI. In a study carried out by Mellén et al (16) , 20 asthmatic patients with airway obstruction received salbutamol via MDI or via Turbuhaler.…”
Section: Discussionmentioning
confidence: 98%
“…Challenge methods are increasingly used to help achieve these conditions. For example, crossover studies of salbutamol Turbuhaler1 and pMDI required 23 patients to assess bronchoprotective effects against methacholine [24], whereas direct assessment of bronchodilation required o40 evaluable patients [7]. Methacholine-induced bronchoconstriction is now widely accepted as a method of increasing the sensitivity of the efficacy end-point in assessing inhaled b 2 -agonists, and was recently validated in a bioequivalence study of HFA and CFC pMDIs [25].…”
Section: Discussionmentioning
confidence: 99%